1997
DOI: 10.1055/s-0038-1657511
|View full text |Cite
|
Sign up to set email alerts
|

Factor VIIa-Tissue Factor: Functional Importance of Protein-Membrane Interactions

Abstract: Overall structure and function of TF-FVlla (1,18,19); it confers the ability to bind reversibly to anionic phospholipids. Next to the Gla-domain, and sometimes classified as part of it, is a short shetch of largely hydrophobic residues called the hydrophobic or aromatic stack. Next are two modules related to epidermal growth factor (EGF domains). EGFr, the more N-terminal of the two, contains a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
35
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 15 publications
(28 reference statements)
4
35
0
Order By: Relevance
“…In support of this proposal, recent fluorescence resonance energy transfer studies demonstrated that the activesite of fVIIa in complex with TF in the extrinsic Xase complex is also located far above the membrane surface (13). Thus, for effective recognition by fVIIa, both fIX and fX must also ‡To whom correspondence should be addressed: Alireza R. Rezaie, Ph.D., Department of Biochemistry and Molecular Biology, St. Louis University School of Medicine, 1402 S. Grand Blvd., St. Louis, MO 63104, Phone: (314) Fax: (314) assemble into the activation complex in the same extended conformations in order to maintain the activation peptides of the substrates at a similar distance to that of the active-site of fVIIa above the membrane surface (2,12,14,15).Like other vitamin K-dependent plasma serine proteases, the structure of fVIIa consists of a light and a heavy chain held together by a disulfide bond (16,17). The N-terminal light chain of fVIIa contains the Gla and two epidermal growth factor (EGF)-like domains and the Cterminal heavy chain contains the trypsin-like catalytic domain of the protease (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this proposal, recent fluorescence resonance energy transfer studies demonstrated that the activesite of fVIIa in complex with TF in the extrinsic Xase complex is also located far above the membrane surface (13). Thus, for effective recognition by fVIIa, both fIX and fX must also ‡To whom correspondence should be addressed: Alireza R. Rezaie, Ph.D., Department of Biochemistry and Molecular Biology, St. Louis University School of Medicine, 1402 S. Grand Blvd., St. Louis, MO 63104, Phone: (314) Fax: (314) assemble into the activation complex in the same extended conformations in order to maintain the activation peptides of the substrates at a similar distance to that of the active-site of fVIIa above the membrane surface (2,12,14,15).Like other vitamin K-dependent plasma serine proteases, the structure of fVIIa consists of a light and a heavy chain held together by a disulfide bond (16,17). The N-terminal light chain of fVIIa contains the Gla and two epidermal growth factor (EGF)-like domains and the Cterminal heavy chain contains the trypsin-like catalytic domain of the protease (16,17).…”
mentioning
confidence: 99%
“…assemble into the activation complex in the same extended conformations in order to maintain the activation peptides of the substrates at a similar distance to that of the active-site of fVIIa above the membrane surface (2,12,14,15).…”
mentioning
confidence: 99%
“…[11][12][13][14] The activated platelets provide anionic surfaces for the assembly and catalysis of intrinsic tenase (VIIIa/IXa), prothrombinase (Va/Xa), and XIa complexes, leading to explosive generation of thrombin and consolidation of the fibrin-platelet plug. [15][16][17] Thus, rapid exposure of PS on the cell surfaces of platelets is the key thrombogenic stimulus initiating and propagating the clotting cascade. 9,10,17) Annexins (ANXs) are a family of calcium-dependent phospholipid binding proteins.…”
mentioning
confidence: 99%
“…Tissue factor (TF) 1 is an integral membrane cofactor that upon exposure to circulating blood binds with high affinity to factor VIIa (fVIIa) to catalyze the rapid activation of procoagulant zymogens factors IX and X, thereby initiating the blood clotting cascade (1)(2)(3). The structure of TF is composed of two fibrinonectin type III-like extracellular domains, a single membrane-spanning domain and a short cytoplasmic tail (4,5).…”
mentioning
confidence: 99%
“…The structural data have indicated that the extracellular domains of TF make extensive interactions with both the light and heavy chains of fVIIa (10). It is believed that these interactions allosterically change the conformation of the active-site pocket of fVIIa, leading to a dramatic improvement in the catalytic efficiency of the protease toward both synthetic and natural macromolecular substrates (1). Most of the functionally critical residues of TF have been mapped by the Ala-scanning mutagenesis approaches (7,9,11).…”
mentioning
confidence: 99%